A Review of Pharmacological Treatment Options for Lung Cancer: Emphasis on Novel Nanotherapeutics and Associated Toxicity - G. England, Christopher; F. Ng, Chin; van Berkel, Victor; B. Frieboes, Hermann (Current Drug Targets, 2015)
Lung cancer remains a leading cause of death. Current treatment options are generally ineffective, highlighting the dire need for novel approaches. While numerous biologically-active chemotherapeutics have been discovered in the last two decades, biological barriers including minimal water solubility, stability, and cellular resistance hinder in vivo effectiveness. To overcome these limitations, nanoparticles have been designed to deliver chemotherapeutics selectively to cancerous tissue while minimizing pharmacokinetics hindrance. Numerous studies are underway analyzing the efficacy of nanoparticles in drug delivery, theranostic applications, and photothermal therapy. However, while nanoparticles have shown efficacy in treating some cancers, their potential toxicity and lack of targeting may hinder clinical potential. With the aim to help sort through these issues, we conduct a review to describe recent applications of nanotherapeutics for the treatment and diagnosis of lung cancer. We first provide a detailed background of statistics, etiology, histological classification, staging, diagnosis, and current treatment options. This is followed by a description of current applications of nanotherapeutics, focusing primarily on results published during the past five years. The potential toxicity associated with nanoparticles is evaluated, revealing inconclusive information which highlights the need for further studies. Lastly, recent advances in mathematical modeling and computational simulation have shown potential in predicting tumor response to nanotherapeutics. Thus, although nanoparticles have shown promise in treating lung cancer, further multi-disciplinary studies to quantify optimal dosages and assess possible toxicity are still needed. To this end, nanotherapeutic options currently in clinical trials offer hope to help address some of these critical issues.
Keywords: nanotherapeutics for lung cancer